Lactobacillus rhamnosus GR-1 Ameliorates Escherichia coli-Induced Activation of NLRP3 and NLRC4 Inflammasomes With Differential Requirement for ASC - Wu, Qiong; Zhu, Yao-Hong; Xu, Jin; Liu, Xiao; Duan, Cong; Wang, Mei-Jun; Wang, Jiu-Feng (Frontiers in Microbiology, 2018)
Escherichia coli is a common cause of mastitis in dairy cows. The adaptor protein apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) synergizes with caspase-1 to regulate inflammasome activation during pathogen infection. Here, the ASC gene was knocked out in bovine mammary epithelial (MAC-T) cells using clustered, regularly interspaced, short palindromic repeat (CRISPR)/CRISPR-associated (Cas)-9 technology. MAC-T cells were pre-incubated with and without Lactobacillus rhamnosus GR-1 and then exposed to E. coli. Western blot analysis demonstrated increased expression of NLRP3 and NLRC4 following E. coli infection, but this increase was attenuated by pre-incubation with L. rhamnosus GR-1, regardless of ASC knockout. Western blot and immunofluorescence analyses revealed that pre-incubation with L. rhamnosus GR-1 decreased E. coli-induced caspase-1 activation at 6 h after E. coli infection, as also observed in ASC-knockout MAC-T cells. The E. coli-induced increase in caspase-4 mRNA expression was inhibited by pre-incubation with L. rhamnosus GR-1. ASC knockout diminished, but did not completely prevent, increased production of IL-1β and IL-18 and cell pyroptosis associated with E. coli infection, whereas pre-incubation with L. rhamnosus GR-1 inhibited this increase. Our data indicate that L. rhamnosus GR-1 suppresses activation of ASC-dependent NLRP3 and NLRC4 inflammasomes and production of downstream IL-lβ and IL-18 during E. coli infection. L. rhamnosus GR-1 also inhibited E. coli-induced cell pyroptosis, in part through attenuation of NLRC4 and non-canonical caspase-4 activation independently of ASC.